Molecular Tracing of SARS-CoV-2 in Italy in the First Three Months of the Epidemic - Lai, Alessia; Bergna, Annalisa; Caucci, Sara; Clementi, Nicola; Vicenti, Ilaria; Dragoni, Filippo; Cattelan, Anna; Menzo, Stefano; Pan, Angelo; Callegaro, Annapaola; Tagliabracci, Adriano; Caruso, Arnaldo; et al. (Viruses, 2020)
The aim of this study is the characterization and genomic tracing by phylogenetic analyses of 59 new SARS-CoV-2 Italian isolates obtained from patients attending clinical centres in North and Central Italy until the end of April 2020. All but one of the newly-characterized genomes belonged to the lineage B.1, the most frequently identified in European countries, including Italy. Only a single sequence was found to belong to lineage B. A mean of 6 nucleotide substitutions per viral genome was observed, without significant differences between synonymous and non-synonymous mutations, indicating genetic drift as a major source for virus evolution. tMRCA estimation confirmed the probable origin of the epidemic between the end of January and the beginning of February with a rapid increase in the number of infections between the end of February and mid-March. Since early February, an effective reproduction number (Re) greater than 1 was estimated, which then increased reaching the peak of 2.3 in early March, confirming the circulation of the virus before the first COVID-19 cases were documented. Continuous use of state-of-the-art methods for molecular surveillance is warranted to trace virus circulation and evolution and inform effective prevention and containment of future SARS-CoV-2 outbreaks.